Hypoxia represses FOXF1 in lung endothelial cells through HIF-1α - Acharya, Anusha; Bian, Fenghua; Gomez-Arroyo, Jose; Wagner, Kimberly A.; Kalinichenko, Vladimir V.; Kalin, Tanya V. (Frontiers in Physiology, 2024)
Forkhead Box F1 (FOXF1) transcription factor plays a critical role in lung angiogenesis during embryonic development and lung repair after injury. FOXF1 expression is decreased in endothelial cells after lung injury; however, molecular mechanisms responsible for the FOXF1 transcript changes in injured lung endothelium remain unknown. We used immunostaining of injured mouse lung tissues, FACS-sorted lung endothelial cells from hypoxia-treated mice, and data from patients diagnosed with hypoxemic respiratory failure to demonstrate that hypoxia is associated with decreased FOXF1 expression. Endothelial cell cultures were used to induce hypoxia in vitro and identify the upstream molecular mechanism through which hypoxia inhibits FOXF1 gene expression. Bleomycin-induced lung injury induced hypoxia in the mouse lung tissue which was associated with decreased Foxf1 expression. Human FOXF1 mRNA was decreased in the lungs of patients diagnosed with hypoxemic respiratory failure. Mice exposed to hypoxia exhibited reduced Foxf1 expression in the lung tissue and FACS-sorted lung endothelial cells. In vitro, hypoxia (1% of O2) or treatment with cobalt (II) chloride increased HIF-1α protein levels but inhibited FOXF1 expression in three endothelial cell lines. Overexpression of HIF-1α in cultured endothelial cells was sufficient to inhibit Foxf1 expression. siRNA-mediated depletion of HIF-1α prevented the downregulation of Foxf1 gene expression after hypoxia or cobalt (II) chloride treatment. Hypoxia inhibits FOXF1 expression in endothelial cells in a HIF-1α dependent manner. Our data suggest that endothelial cell-specific inhibition of HIF-1α via gene therapy can be considered to restore FOXF1 and improve lung repair in patients with severe lung injury.